Investigation of structural and external parameters affecting the efficiency of quantum dot solar cells: A modified detailed-balance model study - Fatih Koc; Carlos A. Duque; Mehmet Sahin (Materials Today Quantum, 2025)
In this study, the power conversion efficiency (PCE) of InP/GaAs/GaSb quantum dot solar cell (QDSC) with type II confinement regime is investigated depending on different structural parameters such as, core radius, spacer layer, and outer shell thickness using both original detailed balance model (ODBM) developed by Shockley and Queisser, and modified detailed balance model (MDBM). Moreover, the effect of external parameters such as temperature and hydrostatic pressure on the PCE is also investigated, and the possible physical reasons are discussed in detail and comparatively. The results show that the MDBM can better reveal the critical effects of the structural parameters, i.e., the size and material properties and the confinement regime on the PCE. A significant result related to this shows that the PCE of the InP/GaAs/GaSb QDSC model can be optimized by adjusting the spacer material thickness to maintain the effective energy gap at different fixed values. At the same time, it is seen that the MDBM is also more successful in determining the effects of external parameters on the PCE. This study develops a novel method of determining the best device parameters by thoroughly investigating the impact of structural and external parameters on the PCE of QDSCs.